Fracture behaviour and numerical study of resistance spot welded joints in high-strength steel sheet. Issue 8 (2nd August 2016) - Sadasue, Teruki; Igi, Satoshi; Taniguchi, Koichi; Ikeda, Rinsei; Oi, Kenji
Abstract: Cross tension tests of resistance spot welded joints with varying nugget diameter were carried out using 980 MPa high strength steel sheet of 1.6 mm thickness. In proportion, as nugget diameter increased from 3√ t to 5√ t (where t is thickness), cross tension strength (CTS) increased while fracture morphology simultaneously transferred from interface fracture to full plug fracture. In cases of interface fracture, circumferential crack initiation due to separation of the corona bond arose at an early stage of loading. The crack opening process without propagation was recognized until just before fracture and then the crack propagated to the nugget immediately in a brittle manner around CTS. In full plug fracture, main ductile crack initiation from the notch-like part at the end of sheet separation occurred with the sub-crack initiated at an early stage. The ductile crack propagated toward the HAZ and base material to form full plug fracture. The mode I stress intensity factor was considered as a suitable fracture parameter because the circumferential crack behaved pre-crack for brittle fracture in the nugget region at the final stage. Based on the FE analysis, the mode I stress intensity factor was calculated as 116 MPa √ m at CTS as fracture toughness for the nugget. With respect to full plug fracture, ductile crack initiation behaviour from the notch-like part was expressed by concentration of equivalent plastic strain. On the assumption that the ductile crack arose in critical value of equivalent plastic strain, the value was calculated as 0.34 by FE analysis. Reasonable interpretation for interface fracture and full plug fracture in the resistance spot welded joint was proposed due to first crack initiation by stress concentration, brittle fracture by using mode I stress intensity factor, and ductile crack initiation by using equivalent plastic strain.